(untitled) - Doane, David P. (NewYork, 2001)
Visual Statistics is an interactive multimedia tool designed to teach statistical concepts in a graphical and user-friendly environment. The software consists of 21 topics that are typically covered in an Introductory Statistics or Business Statistics course, and can be found in other courses such as Regression, Quality Control and Forecasting. The software can be used alone or with a textbook. This unique tool fosters "interactive learning" through competency-building exercises, individual and team experiments, relevant examples and built-in databases.
Keywords: Statistics,Khoa học thống kê